Repotenciación del mantenimiento predictivo basado en el análisis de vibración enfocado a equipos rotatorios usados para el proceso de producción de una planta química ubicada en Guayaquil - Ecuador. - Espinoza Ronquillo, Clemente Douglas (2019)
The main objective of the present work is to carry out the respective information survey and current diagnoses to the different rotating equipment based on the vibratory analysis. Repotenciando thus the predictive maintenance to know and identify the most common failures in the rotating equipment caused by, bad alignments, tapping by wear, inadequate temperatures, gears in positions not correct. Also, it is necessary to be clear about the basic concepts associated with vibrations, the measurement sequence, spectra and vibratory diagrams in each of them and the analytical vibratory behavior of the different cases due to faults. On the other hand, perform the due economic study and possible impacts that enclose the margins of convenience where costs are raised by the acquisition teams, personnel with extensive knowledge in the tests of the equipment and training of maintenance personnel on the repowering of predictive maintenance with the appropriate devices. The different types of standards and how they are implemented in the different teams that are associated with the continuous production process. It is considered a review of the benefits and probabilities in an unfavorable way. As a last event, the application of the repowering of predictive maintenance in the system is contemplated, both to the spectra, statistical graphs of processes with a vibratory history and with it the considerations that can be chosen when applying predictive maintenance.